RHEOLOGICAL RESPONSES OF VISCOELASTIC MODELS UNDER DYNAMICAL LOADING - Rajneesh Kakar; Kanwaljeet Kaur; Kishan Chand Gupta (European Scientific Journal, ESJ, 2013)
The purpose of this paper is to study the rheological responses of four and five-parameter viscoelastic models under dynamic loading. These models are chosen for studying elastic, viscous, and retarded elastic responses to shearing stress. The viscoelastic specimen is chosen which closely approximates the actual behavior of a polymer. The module of elasticity and viscosity coefficients are assumed to be space dependent i.e. functions of ''x in non-homogeneous case and stress-strain are harmonic functions of time''t. The complex viscosity of five parameter model is calculated. The expression for relaxation time for five parameters and four parameter viscoelastic models have been obtained by using a constitutive equation. The dispersion equation is obtained by using Ray techniques. The rheological responses for both models under dynamical loading are shown graphically. Also, the five parameter model is justified with the help of cyclic loading for maxima or minima.